An integrated impact of blockchain on supply chain applications - Ieva Meidute-Kavaliauskiene; Bülent Yıldız; Semsettin Çiğdem; Renata Cinčikaitė (Logistics, 2021)
Market conditions have become increasingly dynamic and demanding, resulting in a challenging competitive environment. To adapt to this dynamic environment, supply chains have become increasingly reliant on collaboration, integration, flexibility, and trust between stakeholders. Therefore, the importance of new technological applications in supply chains has grown even more. To improve supply chain flow control, modern specialized applications must be implemented. Blockchain technology has established itself as a necessary component of today's competitive environment. Companies should invest in blockchain technology to respond quickly to changing market conditions and demands in today's dynamic business environment. In this regard, this study investigates the effect of blockchain technology utilization on supply chain transparency, supply chain flexibility, and trust in suppliers. For this purpose, first, data were collected from the first 1000 exporting firms declared in 2019 by the Turkey Exporters Assembly using a survey method. Secondly, factor analyses and regression analyses were performed with the dataset obtained from 84 companies. As a result of the analysis, it was determined that blockchain technology utilization increases transparency, flexibility, and trust in supply chains. According to these results, it is suggested that companies should invest in blockchain technology to make their supply chain more transparent, flexible, and secure. Moreover, blockchain plays a crucial role in building mutual trust with supply chain stakeholders. Finally, the research includes some considerations on the positive implications and potential of blockchain in collaboration and integration.
Keywords: 650; blockchain; supply chain transparency; supply chain flexibility; trust; integration; collaboration